Oxford studies in philosophy of language - LePore, Ernest 1950-; Sosa, David 1966- (Oxford Oxford University Press, 2019)
"Philosophy of language has been at the centre of philosophical research at least since the start of the 20th century. Since that 'linguistic turn' much of the most important work in philosophy has related to language. But till now there has been no regular forum for outstanding original work in this area. That is what Oxford Studies in Philosophy of Language offers. Anyone wanting to know what's happening in philosophy of language could start with these volumes"--
Includes bibliographical references and index.
Keywords: Language and languages -- Philosophy